Hubungan Jenis Kelamin dengan Kualitas Hidup Terkait Kesehatan Pasien Pasca Stroke Iskemik di RSUD Dr. Moewardi - Savitri, Martha Oktavia Dewi; Hartanto, Oemar Sri; Murti, Bhisma (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Stroke has remained the top major killers during this last decade, actually as second leading cause of death in the world. Men suffers more stroke than women, yet the severity is worse in women. Â Based on some literatures, the outcome after stroke is estimated by sex, female patient has poor recovery with greater chance of depression and tends to have more disabilities, impairments and dependencies in functional activities, which these will deteriorate patientâs health related quality of life (HRQOL). Â This study aims to investigate Â whether there is any correlation between sex and health related quality of life of post ischemic stroke patients. Methods: This study was performed using analytic observational method with cross sectional approach. Subjects were post ischemic stroke patients at Public Hospital Dr. Moewardi. Forty five samples were taken by using fixed exposure sampling method. Instruments used in this study were Health Related Quality of Life (HR-QOL) SF-36 and Family Support Instrument. Statistic test used in this study was multiple linear regression analysis. Results: Twenty three samples (51.1 %) were men. The average age of patients is around 59 years, with an average score of HR-QOL= 353.35. It has been found that there is significant negative correlation between female patients and HR-QOL for b= -69.35, p=0.000 (p<0.05). It also has been found that the confounding factor of age is negatively and significantly correlated to the HR-QOL for b= -3.84, p= 0.000 (p<0.05) and the confounding factor of family support has significantly positive correlation to HR-QOL for b= 10.33, p=0.000 (p<0.05). Adjusted R2= 0.95 showing the suitability of the model by 95% in the population. Conclusion: Female patients averagely have lower HR-QOL score as much as 69.35 than male patients. One year increment in age will decrease HR-QOL score as much as 3.84Â points. And each 1-score increase in family support will enhance HR-QOL score as much as 10.33 points. Keywords: sex, age, family support, health related quality of life, post ischemic stroke patientsÂ